A BRIEF REVIEW OF VARIOUS GENDER ANALYSIS METHODOLOGIES - M.Z.Y. Hassan; T. Ali; M. Ahmad (Journal of Animal and Plant Sciences, 2006)
This paper reviews the various methods used for gender analyses in different parts of the world. Every research project had a confined methodology. It may be concluded that both quantitative and qualitative research methods were important in social sciences, but better results were achieved by combining them.
Keywords: Methodologies; quantitative; qualitative; questionnaire.